Density and species composition of Anopheles mosquito larvae along Lake Tana, northwest Ethiopia - Fasil Adugna; Melaku Wale; Endalkachew Nibret; Zena Ameha (Scientific African)
Malaria remains one of the most important diseases in developing countries. Ethiopia is a developing country with about 60 % of the population estimated to be at risk of infection. Therefore, this study determined the density, species composition, and habitat characteristics of Anopheles larvae. A longitudinal study was conducted from January to December 2021 in Lake Tana and its surroundings. Mosquito larvae were sampled using a soup ladle. Late instar larvae were identified as species. A multilevel mixed effect Poisson model was used to assess the association of Anopheles species density and habitat characteristics. In total, 4028 Anopheles larvae were collected from five habitat types, of which swamps were the most populated. Six Anopheles species were identified among which An. gambiae s.l. was the dominant followed by An. pharoensis. The analysis showed that several factors such as habitat permanency, habitat types, vegetation types, sampling months, presence of debris, substrate types, water turbidity, distance to nearby houses, water pH, and depth of habitats were identified as predictor factors for the presence of high-larvae density. In this study, the dominant Anopheles species and factors related to the occurrence and density of Anopheles mosquitoes were identified. Therefore, appropriate management should be implemented on these factors to reduce the density of malaria vectors and hence malaria transmissions.